Silicon nitride sintered body, circuit board, and method for producing silicon nitride sintered body
Patent Information
- Application Number
- JP2023101402
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-06-21
AI Technical Summary
Conventional silicon nitride sintered bodies exhibit etching unevenness and poor dielectric strength due to the presence of a grain boundary crystal phase, leading to non-uniform particle distribution and dielectric breakdown, which can cause equipment damage.
A silicon nitride sintered body with controlled grain boundary phase composition, comprising an amorphous phase and a grain boundary crystal phase with an integrated intensity ratio of 3% or less, and the addition of Group 2 element fluoride to suppress crystallization, resulting in improved etching resistance and dielectric strength.
The solution reduces etching unevenness and enhances dielectric breakdown electric field to 8 kV/mm, ensuring uniform etching and improved mechanical and thermal properties, such as thermal conductivity of 80 W/mK and three-point bending strength of 700 MPa.
Smart Images

Figure 00000019_0000 
Figure 00000020_0000 
Figure 00000020_0001
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicon nitride sintered body, a circuit board, and a method for producing a silicon nitride sintered body. [Background technology]
[0002] In recent years, the heat generation density of power modules has increased with the increasing density and power output of electronic devices and semiconductor devices. The temperature rise of a power module can cause malfunction of elements and cracks in the insulated circuit board. For this reason, ceramic substrates such as alumina and aluminum nitride, which are materials with relatively high thermal conductivity, have been used for insulated circuit boards. However, alumina and aluminum nitride have the disadvantage of low mechanical strength. Therefore, thick copper, which is subject to strong thermal stress, cannot be directly bonded to a ceramic substrate, which has restricted the structure of power modules. Specifically, a problem is that the power module becomes larger because it is necessary to solder a heat sink such as copper or aluminum to the insulated circuit board. Therefore, silicon nitride (Si 3 N 4 ) material. Silicon nitride sintered bodies have higher strength and fracture toughness than alumina and aluminum nitride sintered bodies, making it possible to directly bond thick copper to insulated circuit boards, which contributes to the miniaturization of modules. For this reason, silicon nitride sintered bodies with improved thermal conductivity as well as mechanical strength are being developed.
[0003] For example, Patent Document 1 discloses a method for producing a silicon nitride sintered body substrate with improved mechanical properties and thermal conductivity. In this method, 1 to 15% by weight of a sintering aid of one or more elements selected from Mg, Ca, Sr, Ba, Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, and Yb is added to silicon nitride powder containing 0.1% by weight or less of Al, and the resulting mixture is molded and then fired at a temperature of 1700°C to 2300°C under a nitrogen gas pressure of 1 to 500 atm. The silicon nitride sintered body substrate obtained by this method is composed of 85% to 99% by weight of β-type silicon nitride grains and the remainder being a grain boundary phase of oxide or oxynitride. The grain boundary phase contains 0.5% to 10% by weight of one or more metal elements selected from Mg, Ca, Sr, Ba, Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, and Yb. The grain boundary phase contains 1% by weight or less of Al atoms, has a porosity of 5% or less, and in the microstructure of the sintered body, the proportion of β-type silicon nitride grains having a minor axis diameter of 5 μm or more is 10% to 60% by volume. In other words, it is known that in order to obtain a silicon nitride sintered body substrate with high thermal conductivity, rare earth compounds and magnesium oxide are added as sintering aids, and the thermal conductivity and mechanical strength can be improved by changing the mixing ratio and amount of them.
[0004] Various metal plates are bonded to the substrate surface of the silicon nitride sintered body, which has both high thermal conductivity and high mechanical strength, in order to form circuits. Direct bonding and active metal methods are used to bond various metal plates (mainly copper plates) to the substrate surface of the silicon nitride sintered body. In the direct bonding method, a copper plate or the like is placed on the substrate and heated to directly bond the substrate and the copper plate. In the active metal method, a ceramic substrate and a copper plate are bonded via a brazing material containing active metals such as Ti, Zr, and Hf. Then, an etching mask is formed in a circuit pattern on the copper plate surface after bonding, and the entire substrate is immersed in an etching solution such as a copper chloride solution or a hydrochloric acid solution, and unnecessary portions of the copper plate (where no etching mask is formed) are etched. Since the characteristics of the substrate surface of the silicon nitride sintered body may change when the substrate surface is exposed to the etching solution, it is desirable for the silicon nitride sintered body to have high etching resistance.
[0005] On the other hand, Patent Document 2 discloses that the etching resistance to acids and alkalis is improved by utilizing the etching-resistant property of the grain boundary crystal phase to increase the ratio of the crystal phase among the amorphous phase and the crystal phase in the grain boundary phase. In addition, Patent Document 2 does not contain rare earth elements that reduce the crystallinity of the grain boundary phase of the silicon nitride sintered body, and further promotes the crystallization of the grain boundary phase by adding particles containing elements of Ti, Zr or Hf. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 9-30866 [Patent Document 2] JP 2016-64971 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in conventional silicon nitride sintered body substrates (even in silicon nitride sintered bodies containing rare earth elements as in Patent Document 1), the grain boundary crystal phase in the grain boundary phase exists to a certain extent, which may cause uneven etching (or etching residue) in the grain boundary crystal phase of the silicon nitride sintered body, which may cause poor appearance of the substrate surface after etching. In particular, when the proportion of the grain boundary crystal phase is increased to improve etching resistance as in Patent Document 2, this uneven etching becomes even more noticeable. Such uneven etching of the grain boundary crystal phase portion causes non-uniformity in the particle distribution in the substrate, which causes a local decrease in dielectric strength on the substrate surface, which is a problem. In particular, it is known that in circuit substrates, electric field concentration occurs at the end of the wiring pattern, and a discharge path is formed along the insulating substrate surface, leading to dielectric breakdown. This dielectric breakdown phenomenon is called creeping discharge, and may cause damage to equipment, so it is required to improve the dielectric strength of the substrate surface of the silicon nitride sintered body in order to alleviate such electric field concentration.
[0008] The inventors reviewed the conventional manufacturing methods for silicon nitride sintered bodies and focused on controlling the crystallization of the grain boundary phase, with the aim of further improving the substrate properties of silicon nitride sintered bodies.
[0009] In order to solve the above problems, the object of the present invention is to provide a silicon nitride sintered body that reduces etching unevenness on a substrate surface after etching and has improved dielectric strength performance, and a method for producing the same. [Means for solving the problem]
[0010] A silicon nitride sintered body according to one embodiment of the present invention is a silicon nitride sintered body having silicon nitride particles and a grain boundary phase present between the silicon nitride particles, The silicon nitride sintered body substrate is characterized in that after etching treatment, which is obtained by immersing the substrate in a hydrochloric acid solution at 50°C and a mass fraction of 7.8% for 30 minutes, the dielectric breakdown field Vi at the substrate surface is 8 kV / mm or more at room temperature.
[0011] In a further embodiment of the present invention, the silicon nitride sintered body has a weight loss per unit surface area (wd) of 12 μg / mm2 after etching of the silicon nitride sintered body under predetermined etching conditions. 2 is as follows: The weight loss wd is obtained by dividing the difference between the weight of the substrate after etching, which is obtained by immersing the silicon nitride sintered substrate in a hydrochloric acid solution at 50°C and with a mass fraction of 7.8% for 30 minutes, and the weight of the substrate before etching, by the surface area of the substrate.
[0012] The silicon nitride sintered body according to a further embodiment of the present invention is a β-Si 3 N 4 and more preferably, the grain boundary phase is composed of an amorphous phase and a grain boundary crystalline phase, The integrated intensity ratio R of the grain boundary crystal phase is 3% or less, The integrated intensity ratio R is calculated by the following formula: R = (1-Ig / Ia) x 100 (%) and Ig is β-Si 3 N 4 and Ia is the sum of the integrated intensities of all X-ray diffraction peaks indexed by Ib, and Ib is the sum of the integrated intensities of all X-ray diffraction peaks observed.
[0013] The silicon nitride sintered body according to one embodiment of the present invention comprises silicon nitride particles and a grain boundary phase present between the silicon nitride particles, and is a β-Si 3 N 4 A silicon nitride sintered body having an X-ray diffraction peak of the grain boundary phase is composed of an amorphous phase and a grain boundary crystalline phase, The integrated intensity ratio R of the grain boundary crystal phase is 3% or less, The integrated intensity ratio R is calculated by the following formula: R = (1-Ig / Ia) x 100 (%) and Ig is β-Si 3 N 4is the sum of the integrated intensities of all X-ray diffraction peaks indexed by Ia, and Ib is the sum of the integrated intensities of all X-ray diffraction peaks observed.
[0014] A silicon nitride sintered body according to one embodiment of the present invention is a silicon nitride sintered body having silicon nitride particles and a grain boundary phase present between the silicon nitride particles, the grain boundary phase is composed of an amorphous phase and a grain boundary crystalline phase, Under predetermined etching conditions, the weight loss per unit surface area of the substrate after etching of the silicon nitride sintered body is 12 μg / mm 2 is as follows: The weight loss amount wd is obtained by dividing the difference between the weight of the substrate after etching, which is obtained by immersing the silicon nitride sintered substrate in a hydrochloric acid solution at 50°C and with a mass fraction of 7.8% for 30 minutes, and the weight of the substrate before etching, by the surface area of the substrate.
[0015] The silicon nitride sintered body according to a further embodiment of the present invention is more preferably further characterized in that the integrated intensity ratio R of the grain boundary crystal phase is 0.3 to 3%.
[0016] The silicon nitride sintered body according to a further embodiment of the present invention is more preferably further characterized in that it contains 0.02 to 0.2% by weight of calcium element.
[0017] The silicon nitride sintered body according to a further embodiment of the present invention is further characterized by more preferably containing 0.05 to 0.2% by weight of elemental fluorine.
[0018] A silicon nitride sintered body according to a further embodiment of the present invention is more preferably further characterized in that, in a SEM cross-sectional image of the substrate after the etching treatment, the grain boundary phase has been removed to a depth of less than 40 μm from the substrate surface, and no grain boundary crystal phase remains in the region from which the grain boundary phase has been removed.
[0019] The silicon nitride sintered body of a further embodiment of the present invention is further characterized by being composed of 1 to 5 weight percent yttrium oxide, 1.5 to 3.5 weight percent magnesium oxide, and 0.05 to 0.3 weight percent of a Group 2 element fluoride. The Group 2 element fluoride is preferably CaF 2 and MgF 2 It is more preferred to select from the group consisting of:
[0020] A method for producing a silicon nitride sintered body according to one embodiment of the present invention is a method for producing a silicon nitride sintered body, comprising the steps of: mixing silicon nitride powder, rare earth oxide powder, magnesium oxide powder, and Group 2 element fluoride powder in a predetermined mixing ratio and adding a solvent to form a slurry; forming the slurry into a sheet having a predetermined thickness; and sintering the sheet compact in a non-oxidizing atmosphere to obtain a silicon nitride sintered body.
[0021] The method for producing a silicon nitride sintered body according to a further embodiment of the present invention is more preferably further characterized in that the fluorine content of the silicon nitride powder is 800 ppm or less.
[0022] The method for producing a silicon nitride sintered body according to a further embodiment of the present invention is further more preferably characterized in that the mixture of raw material powders has a fluorine content of 600 ppm or more.
[0023] The method for producing a silicon nitride sintered body according to a further embodiment of the present invention is further preferably further characterized in that the Group 2 element fluoride is present in an amount of 0.05% by weight or more in the compounding ratio of the raw material powder.
[0024] In a further embodiment of the present invention, the method for producing a silicon nitride sintered body further comprises the step of: 2 and MgF 2 The compound is further characterized in that it is selected from the group consisting of:
[0025] A further embodiment of the method for producing a silicon nitride sintered body according to the present invention is more preferably characterized by comprising mixing 1 to 5 weight % of yttrium oxide powder, 1.5 to 3.5 weight % of magnesium oxide powder, and 0.05 to 0.3 weight % of a Group 2 element fluoride powder.
[0026] A silicon nitride sintered body according to one embodiment of the present invention is a silicon nitride sintered body having silicon nitride particles and a grain boundary phase present between the silicon nitride particles, The silicon nitride sintered body substrate is immersed in a hydrochloric acid solution at 50° C. and a mass fraction of 7.8% for 30 minutes, and the etching depth ratio R D is 10% or less.
[0027] A silicon nitride sintered body according to one embodiment of the present invention is a silicon nitride sintered body having silicon nitride particles and a grain boundary phase present between the silicon nitride particles, The substrate of the silicon nitride sintered body is immersed in a hydrochloric acid solution at 50° C. and a mass fraction of 7.8% for 30 minutes, and the substrate after etching is obtained. The boundary length ratio R, which indicates the ratio of the length of the boundary between the non-etched layer and the etched layer to the evaluation length L, is L is less than 2.0. Effect of the Invention
[0028] The silicon nitride sintered body and the method for producing the same of the present invention make it possible to reduce etching unevenness on the substrate surface of the silicon nitride sintered body after etching treatment, and to improve the dielectric strength performance. [Brief description of the drawings]
[0029] [Figure 1] 4 shows X-ray diffraction patterns of the silicon nitride sintered bodies of Example 1, Comparative Example 1, and Comparative Example 3. [Diagram 2] (a) SEM image of the cross section of the substrate surface after etching of the silicon nitride sintered body of Example 1 taken at 250x magnification, and (b) an image of the non-etched layer extracted by image processing of the SEM photograph of the substrate cross section after etching. [Diagram 3] (a) SEM image of the cross section of the substrate surface after etching of the silicon nitride sintered body of Comparative Example 1 taken at 250x magnification, and (b) image of the non-etched layer extracted by image processing of the SEM photograph of the substrate cross section after etching. [Figure 4] (a) SEM image of the cross section of the substrate after etching of the silicon nitride sintered body of Comparative Example 3 taken at 250x magnification, and (b) an image of the non-etched layer extracted by image processing of the SEM photograph of the cross section of the substrate after etching. [Diagram 5] FIG. 2 is a schematic diagram showing a method for measuring a dielectric breakdown field in the present invention. [Figure 6] FIG. 2 is a schematic diagram for explaining a method for calculating an etching depth, an etching length ratio, and a boundary line length in the analysis of an SEM image of the silicon nitride sintered substrate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] The silicon nitride sintered body according to one embodiment of the present invention has a substrate shape of a predetermined thickness, and can be used as a circuit substrate for mounting electronic components by brazing (brazing or soldering) a metal plate such as a copper plate to the substrate surface, and etching the metal plate into a circuit shape. In particular, the entire substrate of the silicon nitride sintered body with the metal plate bonded thereto is immersed in an etching solution such as a copper chloride solution or a hydrochloric acid solution for a predetermined time, whereby the metal plate is removed except for the etching mask such as a resist material, and a predetermined circuit is formed on the substrate surface. Electronic devices for various applications are constructed by mounting electronic components such as semiconductor chips on the circuit substrate of this silicon nitride sintered body. In general, it is known that the silicon nitride sintered body is affected by the etching solution over its surface area, and the dielectric breakdown electric field Vi on the substrate surface is reduced by the etching process. The silicon nitride sintered body according to this embodiment has improved etching resistance in terms of unevenness in etching and / or dielectric breakdown electric field compared to conventional ones.
[0031] The thickness of the silicon nitride sintered body substrate of this embodiment is preferably 0.1 to 1.0 mm. In other words, the surface area of the side surface of the substrate is configured to be sufficiently small compared to the combined surface area of the front and back surfaces of the substrate, and the effect of etching on the thickness of the substrate can be ignored in performance evaluation.
[0032] The silicon nitride sintered body of this embodiment is composed of 1 to 5 wt % of rare earth oxide (first sintering aid), 1.5 to 3.5 wt % of magnesium oxide (second sintering aid), 0.05 to 0.3 wt % of Group 2 element fluoride, and the balance is composed of Si 3 N 4 In other words, the silicon nitride sintered body of this embodiment is obtained by sintering a slurry mixture of raw material powders in which silicon nitride powder, rare earth oxide powder, magnesium oxide powder, and Group 2 element fluoride powder are mixed in a predetermined blending ratio.
[0033] In this embodiment, the sintering aid is a combination of oxides of rare earth elements (Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, Yb) as the first sintering aid and magnesium oxide (MgO) as the second sintering aid. In particular, by adding Mg component together with rare earth oxide as the sintering aid component, the liquid phase generation temperature during sintering can be lowered and sinterability can be improved. Furthermore, the first sintering aid is 1 to 5 wt % of Y. 2 O 3 and the second sintering aid is more preferably 1.5 to 3.5 wt % MgO. It has been known from past findings that the use of Mg and Y as sintering aid components makes the silicon nitride sintered body dense, and as a result, it is possible to achieve both relatively high thermal conductivity and mechanical strength. In this embodiment, MgO and Y are used as sintering aids. 2 O 3 It is known from past experience that the rare earth oxide composition ratio does not significantly affect the properties of the silicon nitride sintered body substrate if it is within the range of 1 to 5% by weight, so a person skilled in the art can freely select the type and composition ratio.
[0034] In the sintering process of silicon nitride sintered body, the surface silica layer (SiO 2 ) and Y added as a sintering aid. 2 O 3 and a liquid phase of MgO are generated. After α-type silicon nitride dissolves in the generated liquid phase, it is reprecipitated as β-type silicon nitride when the nitrogen concentration in the liquid crystal increases, and the particles are rearranged in the liquid phase, resulting in densification. The sintering process is generally performed in the temperature range of 1800°C to 1900°C, and crystallization of the grain boundary phase occurs in the cooling process after the sintering process. The inventors focused on suppressing crystallization of the grain boundary phase in the cooling process in order to suppress a decrease in the dielectric breakdown field after the etching treatment (or after the etching process). However, with conventional technology, it was difficult to effectively control the rate of crystallization of the grain boundary phase in the cooling process.
[0035] In the present invention, by adding a Group 2 element fluoride as an additive to the raw material, it is possible to effectively control the crystallization of the grain boundary phase of the sintered body in order to suppress uneven etching of the substrate surface, regardless of the fluorine content (amount of impurities) of the silicon nitride powder. In other words, the silicon nitride sintered body reduces uneven etching and improves the dielectric strength performance and etching resistance of the silicon nitride sintered body on the substrate surface after etching. Here, the Group 2 element fluoride is one or more selected from the group consisting of fluorides of Mg, Ca, Sr, and Ba. In particular, the Group 2 element fluoride is CaF 2 , MgF 2 or a combination thereof. The Group 2 element fluoride is preferably CaF 2 When the fluoride of a group 2 element is MgF, it is considered that the Ca ions and F ions introduced into the liquid phase during firing remain in the grain boundary phase even after sintering, lowering the solidification temperature of the grain boundary phase and making it easier to suppress grain boundary crystallization. 2In the case where the silicon nitride sintered body contains Mg, Mg ions promote the densification of the sintered body in the same manner as MgO. The silicon nitride sintered body of the present embodiment is preferably configured to contain 0.05 to 0.2% by weight of fluorine element. The silicon nitride sintered body of the present embodiment more preferably contains 0.02 to 0.2% by weight of calcium element. The calcium content is preferably CaF 2 It can be calculated based on the blending amount.
[0036] The silicon nitride sintered body of the present embodiment includes a large number of silicon nitride grains and a grain boundary phase existing between the silicon nitride grains. In addition, the silicon nitride sintered body has a β-Si 3 N 4 The grain boundary phase is composed of an amorphous phase and a grain boundary crystalline phase. The integrated intensity ratio R of the grain boundary crystalline phase is 3% or less as an index showing the proportion of the grain boundary crystalline phase in the grain boundary phase (i.e., the degree of crystallization). The integrated intensity ratio R is expressed by the following formula: R = (1 - Ig / Ia) x 100 (%). Ig is β-Si 3 N 4 is the sum of the integrated intensities of all X-ray diffraction peaks indexed by Ia, and Ia is the sum of the integrated intensities of all X-ray diffraction peaks observed. The integrated intensity ratio R of the grain boundary crystal phase is preferably 0.3 to 3%.
[0037] The silicon nitride sintered body of this embodiment can also achieve both high thermal conductivity and high mechanical strength. Specifically, the silicon nitride sintered body of this embodiment preferably has a thermal conductivity of 80 W / mK or more and a three-point bending strength of 700 MPa or more.
[0038] To evaluate the etching resistance of the silicon nitride sintered body, the body was etched under specific etching conditions (immersion in a hydrochloric acid solution with a mass fraction of 7.8% at 50°C for 30 minutes). The weight loss per unit surface area of the silicon nitride sintered body after etching was 12 μg / mm 2The weight loss amount wd is obtained by dividing the difference between the weight of the substrate after etching, which is obtained by immersing the silicon nitride sintered body substrate in a hydrochloric acid solution at 50°C and a mass fraction of 7.8% for 30 minutes, and the weight of the substrate before etching, by the surface area of the substrate. As described later, the weight loss amount wd, which indicates the amount of etching, is reduced compared to conventional silicon nitride sintered bodies that do not contain a Group 2 element fluoride. In other words, the silicon nitride sintered body of this embodiment has higher etching resistance.
[0039] In addition, in the SEM cross-sectional image (see FIG. 2) of the silicon nitride sintered body substrate after the etching process, the grain boundary phase is removed from the substrate surface layer to a depth of less than 40 μm. On the other hand, it has been found that in the conventional silicon nitride sintered body not containing a group 2 element fluoride, the grain boundary phase is removed from the substrate surface layer to a depth of 40 μm or more (see FIG. 3 and FIG. 4). As shown in FIG. 6, this etching depth D (μm) can also be quantitatively evaluated by the average value of the maximum distance (D1max, D2max) and the minimum distance (D1min, D2min) from the substrate front and back surfaces to the boundary line of the grain boundary phase remaining after etching in the evaluation length L of the substrate cross section of the silicon nitride sintered body. In addition, as shown in FIG. 2, no grain boundary crystal phase remains in the surface layer region from which the grain boundary phase of the silicon nitride sintered body of this embodiment has been removed. On the other hand, as shown in FIG. 3 and FIG. 4, in the conventional silicon nitride sintered body not containing a group 2 element fluoride, etching residue can be confirmed in the surface layer region. That is, in the silicon nitride sintered body of this embodiment, unevenness in etching in the surface layer region of the substrate surface after etching is reduced.
[0040] Furthermore, as an index for evaluating the unevenness of etching of the silicon nitride sintered body substrate after etching treatment, the etching depth ratio R D , and / or the boundary length ratio R L can be used.
[0041] Etching depth ratio R Dindicates the ratio (%) of the difference between the etching depth D1 on the front side of the substrate and the etching depth D2 on the back side of the substrate to the average etching depth D on the front and back sides of the substrate, and is expressed by the following formula: R D =|D1-D2| / D The etching depth ratio R D It is estimated that the smaller the etching depth ratio R is, the smaller the variation in etching between the front and rear surfaces of the substrate is, and the smaller the etching unevenness is. D is preferably 10% or less.
[0042] Boundary length ratio R L indicates the ratio of the length of the boundary between the non-etched layer and the etched layer to the evaluation length L, and is expressed by the following formula: R L =(L1+L2) / 2L where L1 is the boundary line length on the front side of the substrate, and L2 is the boundary line length on the back side of the substrate. L It is estimated that the smaller the boundary length ratio R, the less uneven the boundary surface between the non-etched layer and the etched layer, and the less uneven the etching. L is preferably less than 2.0.
[0043] The silicon nitride sintered body has a dielectric breakdown field Vi of 8 kV / mm or more at room temperature or room temperature (measurement environment of 25°C) on the substrate after etching. On the other hand, it is known that the conventional silicon nitride sintered body not containing a group 2 element fluoride as shown in FIG. 3 has a dielectric breakdown field Vi of less than 8 kV / mm on the substrate surface at room temperature or room temperature (measurement environment of 25°C). That is, the silicon nitride sintered body of this embodiment has improved dielectric strength performance compared to the conventional one. Here, the dielectric breakdown field Vi (V / mm) was evaluated as follows. Two independent copper plate electrodes A and B were printed by sputtering on the substrate surface of the silicon nitride sintered body after etching so as to be separated by a minimum distance (see FIG. 5). Then, an alternating current was applied to the electrodes in a fluorine-based inert liquid (Fluorinert) at 25°C, the voltage at which the insulation was broken down was measured, and the measured value was divided by the minimum distance to obtain the dielectric breakdown field Vi (V / mm).
[0044] Next, Group 2 element fluorides (CaF 2 This paper discusses the change in the properties of sintered silicon nitride due to the addition of CaF 2 During the sintering process of the mixture (sheet compact) to which the powder is added in a specified amount, Ca ions and F ions are added to the liquid phase composition of the oxynitride glass. Ca ions form a eutectic compound with the oxynitride glass containing Si and Mg, which has the effect of lowering the melting point of the glass. In addition, by introducing F ions into the oxynitride glass, the nitrogen solubility in the liquid phase is increased, lowering the glass melting point, and two F ions replace one O ion, lowering the degree of polymerization of the glass molecules and lowering the viscosity of the liquid phase. These effects lower the starting temperature for densification in the early sintering of the liquid phase, improve the uniformity of the grain boundary glass layer, and promote densification in the early sintering stage. If densification is advanced at the early sintering stage, the shrinkage rate observed during the heating process from the middle sintering stage to the late sintering stage is smaller than the shrinkage rate from the compact observed during the entire sintering process from the early sintering stage to the late sintering stage. During the heating process from the middle sintering stage to the late sintering stage, MgO and SiO 2The volatilization of the sintered body can easily cause a decrease in the amount of liquid phase and an increase in viscosity, so promoting densification in the early stages of sintering is effective in creating a fine structure for the sintered body and improving the uniformity and characteristics on the front and back surfaces of the substrate and within the substrate.
[0045] Regarding the effect on suppressing grain boundary crystallization, Ca ions and F ions introduced into the liquid phase remain in the grain boundary phase even after sintering, lowering the solidification temperature of the grain boundary phase and making it easier to suppress grain boundary crystallization.
[0046] Regarding the effect on etching resistance, Si 3 N 4 -SiO 2 -Y 2 O 3 The liquid phase formed by CaF 2 It is believed that the dissolution of isothermal oxygen increases the nitrogen concentration in the liquid phase, and the grain boundary phase in a sintered body produced under these conditions has a low oxygen concentration. It is also believed that the etching resistance is improved by the formation of passive chlorides on the surface of the grain boundary glass phase during the acid treatment with hydrochloric acid.
[0047] Regarding the effect on the breakdown electric field, leakage current occurs due to the influence of chlorides formed on the surface of the grain boundary glass phase, which has the effect of reducing the voltage applied between the electrodes on the substrate surface. In addition, etching residues that occur when the crystallization rate of the grain boundary crystal phase is high cause unevenness in the particle distribution in the substrate, which is a factor in causing partial concentration of the electric field. Therefore, by keeping the crystallization rate of the grain boundary crystal phase low, it is possible to suppress the local decrease in the dielectric breakdown electric field.
[0048] Next, the method for producing the silicon nitride sintered body of this embodiment will be described. The method for producing the silicon nitride sintered body mainly includes a step of mixing silicon nitride powder, rare earth oxide powder, magnesium oxide powder, and Group 2 element fluoride powder in a predetermined compounding ratio and adding a solvent to form a slurry, a step of forming the slurry into a sheet molded body of a predetermined thickness, and a step of sintering the sheet molded body in a non-oxidizing atmosphere to obtain a silicon nitride sintered body. Each step will be described in detail below.
[0049] (1) Slurry formation process 1-5 wt% yttrium oxide powder, 1.5-3.5 wt% magnesium oxide powder, and 0.05-0.3 wt% Group 2 element fluoride powder were wet mixed in a mixed solvent of toluene and ethanol using a ball mill with φ10 silicon nitride balls and a nylon pot mill. In the wet mixing, an appropriate amount of dispersant may be added, and typically, a polycarboxylic acid or amine dispersant is added at a concentration of 0.2 mg / m2 relative to the surface area of the raw material powder. 2 to 1.5 mg / m 2 In this mixing step, the grinding and mixing time was adjusted so that the D50 diameter (median diameter) of the Group 2 element fluoride powder was 5 μm or less. After the particle size adjustment of the Group 2 element fluoride powder was completed, 92 to 97.5% by weight of silicon nitride powder was put into the mill and mixed for 12 to 24 hours. Then, a binder, a plasticizer and an organic solvent were added to make a slurry. As a method for adjusting the slurry used for molding, wet mixing using an organic solvent is preferable in order to suppress the productivity and the increase in the amount of oxygen during mixing. As a specific example, a dispersant, an organic solvent mixed with toluene and ethanol is added to the raw material powder, and the mixture is adjusted by a commonly performed mixing and grinding method. Then, the mixture is uniformly mixed and the particle size is adjusted by a method such as a ball mill, a bead mill, or a vibration mill. The slurry is defoamed and viscosity adjusted in a vacuum to a degree that allows the green sheet to be molded. The mill and media used in the mixed grinding method may be made of resins such as urethane and nylon, or ceramics such as silicon nitride and zirconium oxide. In order to prevent impurities from being mixed into the slurry, it is preferable to use resins or silicon nitride.
[0050] Here, the silicon nitride powder is preferably a high-purity silicon nitride powder produced by a direct nitridation method, an imide pyrolysis method, or the like, and has a low oxygen content. On the other hand, the silicon nitride powder contains a certain amount of fluorine as an impurity, but the fluorine content of the silicon nitride powder is preferably 800 ppm or less. Also, the fluorine content of the mixture of raw material powders is preferably 600 ppm or more.
[0051] The rare earth oxide powder may be selected from the oxides of Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, Yb, or combinations thereof. Preferably, the rare earth oxide powder is yttrium oxide (Y 2 O 3 ).
[0052] The group 2 element fluoride powder may be selected from fluorides of Mg, Ca, Sr, and Ba, or a combination thereof. Preferably, the group 2 element fluoride powder is CaF 2 , MgF 2 and combinations thereof.
[0053] (2) Molding process In the molding process, the high-viscosity slurry after viscosity adjustment by vacuum degassing is molded into a sheet, and a green sheet of a specified thickness is obtained by the doctor blade method. The thickness of the green sheet can be appropriately changed depending on the required thickness of the sintered body, but is usually in the range of about 0.1 to 1.3 mm. The molded green sheet is processed into the desired shape by a mold press or a cutting machine to obtain a molded body.
[0054] (3) Firing process The surface of the green body obtained in the molding process is sprayed with boron nitride powder as a release agent, and a block body is prepared by stacking 15 to 30 green bodies. This block body is placed in a boron nitride sheath and degreased in dry air at a temperature range of 500 to 600°C. The degreasing atmosphere may be nitrogen or a vacuum. The degreased block body is fired at a high temperature for a predetermined time to obtain a silicon nitride sintered body, which is the final object of this manufacturing method. The firing process is carried out in a firing furnace in a non-oxidizing (nitrogen) atmosphere at a temperature range of about 1750 to 2000°C. In addition, the Si 3 N 4 In order to prevent volatilization of the sintering aid (eg, MgO), it is preferable to perform the pressure firing under a pressure of 5 atmospheres or more.
[0055] By going through the above-described slurry formation process to the firing process, a silicon nitride sintered body substrate having high etching resistance can be obtained. A metal plate such as a copper plate is brazed (brazed or soldered) to the surface of the silicon nitride sintered body substrate thus produced, an etching mask in the form of a circuit pattern is formed on the surface of the copper plate after bonding, and unnecessary parts of the copper plate are etched with an etching solution such as a copper chloride solution or a hydrochloric acid solution, thereby manufacturing a circuit board. That is, the circuit board can be configured to include a substrate made of a silicon nitride sintered body etched (under the etching conditions of the copper plate) and a metal plate bonded to the surface of the substrate and formed into a predetermined circuit shape by the etching process. In other words, the substrate of the circuit board is the silicon nitride sintered body of this embodiment that has been subjected to an etching process during circuit formation. EXAMPLES
[0056] The present invention will be described in more detail below based on examples and comparative examples, but the present invention should not be construed as being limited to the following examples.
[0057] The silicon nitride sintered bodies according to Examples 1 to 7 and Comparative Examples 1 to 3 were produced under the following conditions and procedures. First, high-purity silicon nitride powder produced by a direct nitriding method was prepared. The silicon nitride powder had an average particle size (D50) of about 0.8 μm and an oxygen content of about 0.8 wt %. MgO powder and Y powder were mixed with the silicon nitride powder in accordance with the compounding composition ratio of each powder. 2 O 3 powder was added in an appropriate amount (Examples 1 to 7, Comparative Examples 1 to 3), and further, CaF 2 Powder and / or MgF 2 A suitable amount of powder (Examples 1 to 7, Comparative Example 2) was added to the mixture. A polycarboxylic acid-based surface-active dispersant was added in an amount of 0.3 mg / m 2Then, about 50 parts by weight of a mixed solvent of toluene and ethanol was added, and the mixture was ground and mixed using silicon nitride balls. Then, 18 parts by weight of polyvinyl butyral as a binder, 6 parts by weight of dioctyl adipate as a plasticizer, and about 20 parts by weight of a mixed solvent of toluene and ethanol were added, and the mixture was stirred and mixed by a ball mill until the binder was completely dissolved and mixed, and a slurry was prepared. Then, the slurry was left in a vacuum, and the viscosity was adjusted by degassing and volatilizing. Next, a sheet molded body was obtained from the prepared slurry by a doctor blade method. The obtained sheet molded body was punched into a shape of 260 mm x 200 mm by die pressing. Then, boron nitride powder was sprayed as a mold release agent on the surface of the punched sheet, and 25 laminates were prepared per block, which were then placed in a boron nitride sheath and heated to 500 ° C in dry air for about 4 hours to remove organic components such as the binder. The sheet compact was then heated in a nitrogen atmosphere at 9 atm for 4 hours at 1860°C to obtain a silicon nitride substrate stack. The silicon nitride substrate stack was separated, the top and bottom substrates were removed, and the peripheries of the remaining 23 substrates were broken using a laser. The boron nitride powder remaining on the substrate surfaces and the droplets that had adhered to the substrate by the laser processing were then removed by honing to obtain a silicon nitride sintered substrate measuring 190mm x 140mm x 0.32mm.
[0058] For each sample, the fluorine content of the mixture of raw material powders before sintering was measured. In addition, for each of the samples (sintered bodies) of Examples 1 to 7 and Comparative Examples 1 to 3, the crystal phase of each sample was identified by X-ray diffraction measurement, and the integrated intensity ratio R of the grain boundary crystal phase was derived by analyzing the X-ray diffraction pattern. Furthermore, for each sample (sintered body), the fluorine content, thermal conductivity (W / mK), and three-point bending strength (MPa) were measured.
[0059] Furthermore, the prepared samples of Examples 1 to 7 and Comparative Examples 1 to 3 were subjected to an etching treatment under the same test conditions, and then their etching resistance performance was evaluated. Specifically, for the samples after the etching treatment, the weight loss per unit surface area wd before and after the etching treatment, and the dielectric breakdown field Vi at the substrate surface were measured. Furthermore, SEM images were taken at 250x magnification of the cut cross section of the sample after the etching treatment. The SEM images were analyzed and observed, and the etching depth D from the substrate surface, the etching depth ratio R between the front and back surfaces of the substrate, and the like were obtained. D , boundary length ratio R L Also, the presence or absence of etching unevenness was evaluated.
[0060] Various measurements and evaluations were performed under the following conditions.
[0061] X-ray diffraction measurement and analysis The X-ray diffraction intensity of each sample was measured by powder X-ray diffraction method using Cu-Kα radiation using an Ultima IV model manufactured by Rigaku Corporation. Individual pieces cut to 15 mm x 15 mm were used for the measurements. The substrate surface was polished to 20 μm or more to prepare the measurement surface. The measurement conditions were as follows. Scan range: 10 degrees to 85 degrees Sampling width: 0.02 degrees Scan speed: 10 degrees / min Divergence slit: 2 / 3 degree Divergence vertical slit: 10mm Scattering slit: 8mm Receiving slit: open Tube voltage / current: 40kV / 40mA Detector: Semiconductor detector In the X-ray diffraction pattern of the substrate plane obtained by irradiating X-rays onto the substrate plane, the integrated intensities of the diffraction peaks corresponding to all the Miller indices (hkl) of the β-type silicon nitride particles were calculated (see the lower panel of Figure 1), and the sum of these was taken as Ig. The Miller indices of the β-type silicon nitride particles are (100), (110), (200), (101), (120), (111), (300), (201), (220), (121), (310), (301), (221), (311), (320), (002), (410), (401), (102), (112), (321), (202), (500), (141), (330), (122), (420), (302), (501), (150), (331), (222), and (421). In addition, the integrated intensities of all the X-ray diffraction peaks observed in the X-ray diffraction pattern were calculated, and the sum of these was defined as Ia. The integrated intensity ratio R of the grain boundary crystal phase was derived using the relational expression R = (1 - Ig / Ia) × 100 (%). Note that the peak search of the measurement data was performed using the integrated powder X-ray analysis software PDXL2.8 (ver. 2.8.4.0) manufactured by Rigaku Corporation under the following conditions. Use peak list and background from template: On Kβ and filter edge removal: On σ cut value: 3.00 Minimum σ cut range: 0.50 Maximum value of σ cut range: 20
[0062] Fluorine content of raw powder mixture The measurements were performed using the pyrohydrolysis separation-ion chromatography method described in JIS R 1603 (2018) using an ion chromatograph Dionex Integrion RFIC manufactured by Thermo Fisher Scientific Inc. and an automatic sample combustion apparatus AQF-2100H manufactured by Nitto Seiko Analytech Co., Ltd.
[0063] Fluorine content of sintered body Qualitative analysis was performed using EZ scan with a Primus IV made by Rigaku Corporation. Individual pieces cut to 25 mm x 25 mm were used for the measurement. The substrate surface was polished to 20 μm or more to prepare the measurement surface, and the measurement diameter was 20 mm.
[0064] Thermal conductivity The flash method was used to measure the thermal conductivity in the thickness direction of the substrate. A thermal conductivity measuring device LFA467 manufactured by NETZSCH Geratebau GmbH was used for the measurements. Pieces cut to 10 mm x 10 mm from the substrate were used for the measurements. A gold sputtered film was formed on both sides of the pieces to reduce the transmission of flash light, and graphene spray was used on both sides of the pieces to uniformly absorb the pulsed light, and a blackening treatment was performed. When calculating the thermal conductivity, a value of 0.68 J / (g·K) was used as the specific heat of the obtained sintered body.
[0065] 3-point bending strength The measuring device was an AG-IS model manufactured by Shimadzu Corporation, and the measurement conditions were a crosshead speed of 0.5 mm / min, a support distance of 30 mm, and the test piece size was 20 mm in width and 0.3 to 0.4 mm in thickness.
[0066] Weight loss per unit surface area after etching The weight of the 40 mm square substrate of the silicon nitride sintered body thus produced was measured, and then it was immersed in a 7.8% by mass hydrochloric acid solution heated to 50°C for 30 minutes, washed with water and dried, and the weight of the substrate was measured again. The value obtained by subtracting the weight after etching from the weight before etching was used as the surface area (3200 mm 2 The weight loss per unit surface area was calculated by dividing the weight loss by the thickness of the side surface (0.32 mm thick). Since the ratio of the surface area occupied by the side surface (thickness 0.32 mm) is extremely small compared to the areas of the front and back surfaces, the thickness was ignored in the calculation formula.
[0067] -Breakdown field of the substrate surface after etching The silicon nitride sintered body thus prepared was immersed in a 7.8% hydrochloric acid solution heated to 50°C for 30 minutes, washed with water and dried. An L / S pattern with a width of 1 mm and a spacing (minimum distance) of 2 mm was then formed on the substrate surface by sputtering (see Figure 5). An AC voltage was applied in Fluorinert at 25°C (room temperature) to measure the breakdown voltage. Measurement terminals were attached to electrodes A and B in Figure 5, and the breakdown voltage was measured using a partial discharge measurement device (Fujikura Dia Cable Partial Discharge Measurement Device A006). Electrodes A and B form a minimum distance at five points, and the voltage value at the time when breakdown occurred at any one of them was measured as the breakdown voltage. The breakdown voltage value was then divided by the distance between the patterns (2 mm) to derive the breakdown electric field.
[0068] Observation of the cross section of the substrate after etching using SEM The silicon nitride sintered body thus prepared was immersed in a 7.8% hydrochloric acid solution heated to 50°C for 30 minutes, washed with water and dried. The substrate was then cut using a diamond cutter or similar device, embedded in epoxy resin, and mirror-polished so that the cross section of the substrate would be the observation surface. A cross-sectional photograph was taken at a magnification of 250x using a JEOL Ltd. JSM-IT700HR scanning electron microscope. In the cross-sectional BSE image of the substrate, the white areas indicate the grain boundary phase. For each sample, the depth from the substrate surface to the surface region where the white areas were removed was defined as the etching depth. In addition, if white lumps were observed in the surface region less than D / 2μm deep from the substrate surface or back surface, it was judged as having uneven etching (×), and if no white lumps were observed, it was judged as having no uneven etching (◯).
[0069] Evaluation of the boundary length ratio between etched and non-etched layers in the substrate cross section, etching depth, and etching depth ratio on the front and back surfaces of the substrate Using the cross-sectional BSE images of the substrate taken at 250 times magnification for each sample, the boundary between the etched layer and the non-etched layer was determined using the image analysis and measurement software WinROOF2021 (ver.5.7.4) manufactured by Mitani Shoji Co., Ltd., and the boundary length and etching depth were calculated based on the boundary. Specifically, the BSE images were imported into WinROOF2021 and various image processing such as filter processing, edge processing, and monochrome imaging were performed. The non-etched layer was then separated by performing binary processing such as binarization and morphology. The analysis of the images from which the non-etched layer was separated was performed on the front and back surfaces of the substrate for each sample. Figure 6 is a schematic diagram explaining the analysis. For the images from which the non-etched layer was separated, the boundary lengths L1 and L2 on the front and back surfaces of the substrate were measured over an arbitrarily set evaluation length L (1000 μm or more). The boundary lengths L1 and L2 represent the length when the boundary between the non-etched layer and the etched layer separated by image processing is stretched to form a single line segment. The boundary length ratio R is calculated by dividing the average of the boundary lengths L1 and L2 on the front and back sides of the board by the evaluation length L. L The boundary length ratio R L is an index showing the degree of waviness of the boundary line relative to the planar direction of the substrate, and it can be interpreted that the larger this value is, the lower the etching uniformity is. L The formula for calculating is as follows: R L =(L1+L2) / 2L Further, the depth direction distance between the front and back surfaces of the substrate and the boundary line was measured over the evaluation length L for both surfaces of the substrate. From the measured depth direction distances, the maximum distance D1max and the minimum distance D1min on the front surface of the substrate were obtained, and their average value was calculated as the etching depth D1 of the front surface of the substrate. Similarly, the maximum distance D2max and the minimum distance D2min on the back surface of the substrate were obtained, and their average value was calculated as the etching depth D2 of the back surface of the substrate. Then, the etching depth D was calculated as the average value of the etching depths D1 and D2 of the front and back surfaces of the substrate. Furthermore, the etching depth ratio R of the front and back surfaces of the substrate was used as an index showing the variation in the etching degree of the front and back surfaces of the substrate. D was calculated. R DThe formula for calculating is as follows: R D =|D1-D2| / D The total evaluation length L is preferably 1000 μm or more. If it is difficult to measure in a single visual field, multiple visual fields may be joined together for calculation.
[0070] Tables 1 and 2 show the conditions and various measurement results for each sample of Examples 1 to 7 and Reference Examples 1 to 3. Table 1 mainly shows the characteristics of the sintered body, and Table 2 mainly shows the etching resistance characteristics. Fig. 1 shows representative X-ray diffraction patterns of Example 1 and Comparative Examples 1 and 3. In the X-ray diffraction patterns, each diffraction peak of β-type silicon nitride particles, indexed by Miller, is shown in the lower column of Fig. 1. Figs. 2 to 4 show representative SEM photographs taken at 250x magnification of the substrate surfaces of the samples of Example 1 and Comparative Examples 1 and 3 after etching treatment.
[0071] [Table 1]
[0072] [Table 2]
[0073] According to Tables 1 and 2, Examples 1 to 7 contain 0.05% by weight or more of CaF 2 and / or MgF 2 Specifically, Examples 1 to 5 differ from Comparative Examples 1 to 3 in that they contain 0.10 to 0.30 wt % CaF 2 Example 6 contains 0.05 wt.% CaF 2 and 0.05 wt.% MgF 2 Example 7 contains 0.20 wt. % MgF 2 On the other hand, Comparative Examples 1 and 3 do not contain a Group 2 element fluoride, and Comparative Example 2 contains a trace amount (0.03 wt%) of CaF 2 Contains:
[0074] As shown in Table 1, the fluorine content of the mixture of raw material powders before firing is 600 ppm or more in Examples 1 to 7, whereas it is less than 600 ppm in Comparative Examples 1 to 3. The fluorine content in Comparative Examples 1 to 3 is mainly due to impurities in the raw material powder of silicon nitride, but the fluorine content due to this raw material powder is 800 ppm or less. Regarding the characteristics of the sintered body, the amount of fluorine (elemental fluorine) contained in the sintered body substrate is 0.05 wt % or more in Examples 1 to 7, whereas it was not detected in Comparative Examples 1 to 3 (i.e., 0 wt %). In other words, it is considered that the elemental fluorine effectively remains in the sintered body by adding an appropriate amount of fluorine as a Group 2 element fluoride.
[0075] FIG. 1 shows the X-ray diffraction patterns of each sample (sintered body substrate). In all samples, the diffraction peaks of β-type silicon nitride particles were confirmed. The diffraction peaks of β-type silicon nitride particles are shown in the lower column of FIG. 1. Meanwhile, in the X-ray diffraction patterns of each sample, diffraction peaks appear at positions other than the diffraction peaks of β-type silicon nitride particles. When the X-ray diffraction patterns of Example 1 and Comparative Examples 1 and 3 are visually compared, diffraction peaks are confirmed in Comparative Examples 1 and 3 at diffraction angles 2θ of 20°, 30°, and 45°, while the diffraction peaks of Example 1 are smaller or cannot be confirmed. In addition, since Examples 2 to 7 showed diffraction patterns with the same tendency as Example 1, illustrations are omitted. Furthermore, when the X-ray diffraction patterns are quantitatively analyzed, as shown in Table 1, the integrated intensity ratio R of the grain boundary crystal phase is 3% or less in Examples 1 to 7, whereas it is greater than 3% in Comparative Examples 1 to 3. More specifically, the integrated intensity ratio R of the grain boundary crystal phase is 0.3 to 3% in Examples 1 to 7. That is, in the silicon nitride sintered bodies of Examples 1 to 7, crystallization in the grain boundary phase is suppressed.
[0076] Furthermore, according to Table 1, it was confirmed that the thermal conductivity was 80 W / mK or more and the three-point bending strength was 700 MPa or more in all of the samples of Examples 1 to 7 and Comparative Examples 1 to 3. In other words, it was found that the addition of an appropriate amount of Group 2 element fluoride did not decrease the properties of thermal conductivity and mechanical strength.
[0077] Table 2 and Figures 2 to 4 show the etching resistance characteristics of each sample. As shown in Table 2, the weight loss amount wd, which indicates the amount of etching per surface area under specified conditions, was 12 μg / mm for Examples 1 to 7. 2 or less, whereas in Comparative Examples 1 to 3, it was 12 μg / mm 2 Moreover, the dielectric breakdown field Vi at room temperature is 8 kV / mm or more in Examples 1 to 7, whereas it is less than 8 kV / mm in Comparative Examples 1 to 3. That is, it was confirmed that, in the silicon nitride sintered bodies of Examples 1 to 7, crystallization in the grain boundary phase is suppressed, while the etching amount is reduced, and further, the dielectric breakdown field Vi of the substrate surface after the etching process is improved.
[0078] 2 to 4 are SEM images (BSE images at 250x magnification) of the cross section of the sintered substrate after etching, in which the white areas indicate the grain boundary crystal phase, and no grain boundary crystal phase is present in other areas. In the unetched deep part of the substrate, the white areas are uniformly present, indicating that the grain boundary crystal phase has not been etched. On the other hand, it is apparent that in the surface region at a predetermined depth from the substrate surface, the white areas have been removed by the etching. According to Table 2 and Figs. 2 to 4, the etching depth D of the comparative example is significantly greater than the etching depth D of the embodiment, and furthermore, the etching depth ratio R of the comparative example on the front and back surfaces of the substrate is 100%. D More specifically, the etching depth D of the silicon nitride sintered bodies of Examples 1 to 7 is less than 40 μm (about 32 to 36 μm), and the etching depth ratio R D is 10% or less, whereas in Comparative Examples 1 to 3, the etching depth D is greater than 40 μm (about 43 to 46 μm) and the etching depth ratio R D is greater than 10%. Also, the boundary length ratio R L Regarding the boundary length ratio R of the silicon nitride sintered bodies of Examples 1 to 7, L is less than 2.0 (about 1.5 to 1.6), whereas in Comparative Examples 1 to 3, the boundary line length ratio R Lis 2.0 or more (about 2.0 to 2.1). Furthermore, it was confirmed that in Examples 1 to 7, no grain boundary crystal phase remains in the surface region at a surface depth of less than D / 2, whereas in Comparative Examples 1 to 3, the grain boundary crystal phase remains without being etched. These SEM observation and analysis results also support the improvement of the etching resistance of the silicon nitride sintered body of the present invention and the improvement of the dielectric breakdown electric field Vi of the substrate surface.
[0079] The present invention is not limited to the above-described embodiment, and can be embodied in various forms within the technical scope of the present invention.
Claims
1. A silicon nitride sintered body having silicon nitride particles and a grain boundary phase present between the silicon nitride particles, A silicon nitride sintered body, characterized in that, after etching treatment of the substrate obtained by immersing the substrate in a hydrochloric acid solution at 50°C and a mass fraction of 7.8% for 30 minutes, the dielectric breakdown field Vi at the substrate surface is 8 kV / mm or more at room temperature.
2. The weight loss per unit surface area of the silicon nitride sintered body after etching under predetermined etching conditions is 12 μg / mm 2 is as follows: The silicon nitride sintered body according to claim 1, characterized in that the weight loss wd is obtained by dividing the difference between the weight of the substrate after etching, obtained by immersing the substrate of the silicon nitride sintered body in a hydrochloric acid solution at 50°C and a mass fraction of 7.8% for 30 minutes, and the weight of the substrate before etching, by the surface area of the substrate.
3. The β-Si alloy comprises silicon nitride particles and a grain boundary phase present between the silicon nitride particles. 3 N 4 A silicon nitride sintered body having an X-ray diffraction peak of the grain boundary phase is composed of an amorphous phase and a grain boundary crystalline phase, The integrated intensity ratio R of the grain boundary crystal phase is 3% or less, The integrated intensity ratio R is expressed by the following formula: R=(1-Ig / Ia)×100(%) and Ig is β-Si 3 N 4 and Ia is the sum of the integrated intensities of all X-ray diffraction peaks indexed by Ib, and Ib is the sum of the integrated intensities of all X-ray diffraction peaks observed.
4. 4. The silicon nitride sintered body according to claim 3, wherein the integrated intensity ratio R of the grain boundary crystal phase is 0.3 to 3%.
5. A silicon nitride sintered body having silicon nitride particles and a grain boundary phase present between the silicon nitride particles, the grain boundary phase is composed of an amorphous phase and a grain boundary crystalline phase, The weight loss per unit surface area of the silicon nitride sintered body after etching under predetermined etching conditions is 12 μg / mm 2 is as follows: The weight loss amount wd is obtained by dividing the difference between the weight of the substrate after etching, which is obtained by immersing the substrate of the silicon nitride sintered body in a hydrochloric acid solution at 50°C and with a mass fraction of 7.8% for 30 minutes, and the weight of the substrate before etching, by the surface area of the substrate.
6. 6. The silicon nitride sintered body according to claim 1, further comprising 0.02 to 0.2% by weight of calcium element.
7. 6. The silicon nitride sintered body according to claim 1, further comprising 0.05 to 0.2% by weight of elemental fluorine.
8. 6. The silicon nitride sintered body according to claim 1 or 5, characterized in that in a SEM cross-sectional image of the substrate after the etching treatment, the grain boundary phase has been removed to a depth of less than 40 μm from the substrate surface, and no grain boundary crystal phase remains in the region from which the grain boundary phase has been removed.
9. The silicon nitride sintered body according to any one of claims 1 to 5, characterized in that it is composed of 1 to 5 wt% yttrium oxide, 1.5 to 3.5 wt% magnesium oxide, and 0.05 to 0.3 wt% Group 2 element fluoride.
10. A method for producing a silicon nitride sintered body, comprising the steps of: mixing silicon nitride powder, rare earth oxide powder, magnesium oxide powder, and Group 2 element fluoride powder in a predetermined mixing ratio and adding a solvent to form a slurry; forming the slurry into a sheet having a predetermined thickness; and a step of sintering the sheet compact in a non-oxidizing atmosphere to obtain a silicon nitride sintered body.
11. 11. The method according to claim 10, wherein the silicon nitride powder has a fluorine content of 800 ppm or less.
12. 11. The method according to claim 10, wherein the fluorine content of the mixture of raw material powders is 600 ppm or more.
13. 11. The method according to claim 10, wherein the Group 2 element fluoride is present in an amount of 0.05% by weight or more in the raw material powder.
14. The Group 2 element fluoride is CaF 2 and MgF 2 11. The method of claim 10, wherein the compound is selected from the group consisting of:
15. 15. The method of any one of claims 10 to 14, comprising mixing 1-5 wt. % yttrium oxide, 1.5-3.5 wt. % magnesium oxide, and 0.05-0.3 wt. % Group 2 fluoride powder.
16. 6. A circuit board comprising: a substrate of the silicon nitride sintered body according to claim 1; and a metal plate bonded onto a surface of the substrate and formed into a predetermined circuit shape.